Embodied intersubjective engagement in mother–infant tactile communication: a cross-cultural study of Japanese and Scottish mother–infant behaviors during infant pick-up - Negayama, Koichi; Delafield-Butt, Jonathan T.; Momose, Keiko; Ishijima, Konomi; Kawahara, Noriko; Lux, Erin J.; Murphy, Andrew; Kaliarntas, Konstantinos (Frontiers in Psychology, 2015)
This study examines the early development of cultural differences in a simple, embodied, and intersubjective engagement between mothers putting down, picking up, and carrying their infants between Japan and Scotland. Eleven Japanese and ten Scottish mothers with their 6- and then 9-month-old infants participated. Video and motion analyses were employed to measure motor patterns of the mothers’ approach to their infants, as well as their infants’ collaborative responses during put-down, pick-up, and carry phases. Japanese and Scottish mothers approached their infants with different styles and their infants responded differently to the short duration of separation during the trial. A greeting-like behavior of the arms and hands was prevalent in the Scottish mothers’ approach, but not in the Japanese mothers’ approach. Japanese mothers typically kneeled before making the final reach to pick-up their children, giving a closer, apparently gentler final approach of the torso than Scottish mothers, who bent at the waist with larger movements of the torso. Measures of the gap closure between the mothers’ hands to their infants’ heads revealed variably longer duration and distance gap closures with greater velocity by the Scottish mothers than by the Japanese mothers. Further, the sequence of Japanese mothers’ body actions on approach, contact, pick-up, and hold was more coordinated at 6 months than at 9 months. Scottish mothers were generally more variable on approach. Measures of infant participation and expressivity indicate more active participation in the negotiation during the separation and pick-up phases by Scottish infants. Thus, this paper demonstrates a culturally different onset of development of joint attention in pick-up. These differences reflect cultures of everyday interaction.